Mutual Legal Assistance sebagai Instrumen Pemberantasan Kejahatan Transnasional dalam Bidang Perpajakan - Alghazali, Muhammad Syammakh Daffa; Siagian, Abdhy Walid (AML/CFT Journal : The Journal Of Anti Money Laundering And Countering The Financing Of Terrorism, 2024)
The circulation of illicit money is still a concern for Indonesia in realizing equitable welfare for all people. One of the sources of illicit money circulating in Indonesia comes from tax evasion, where the source can come from within or outside the country. Tax evasion is actually inseparable from money laundering, which is a sophisticated crime that requires special treatment in its enforcement. This research tries to examine mutual legal assistance (MLA) as an instrument in law enforcement on cross-border tax evasion. This study uses normative legal research methods with a statute approach and a conceptual approach and is descriptive research.  This research shows that the crime of tax evasion cannot be separated from money laundering and can be carried out across countries. To overcome this, MLA is one of the recommendations for the prevention and eradication of anti-corruption from transnational tax crimes in Indonesia. Unfortunately, this MLA approach has not been implemented effectively and efficiently because Indonesia does not have strong regulations related to asset confiscation.